A practical controller design of distributed energy resources for stabilization of interconnected power system based on synchronized phasor measurements - Dechanupaprittha, S.; Watanabe, M.; Mitani, Y.; Hongesombut, K.; Ngamroo, I. (My University, 2009)
With today's advanced technologies, various types of distributed energy resources (DERs) with relatively fast controllability option have been brought into practical applications. This paper presents a metaheuristic-based controller design of controllable DER for stability enhancement based on synchronized phasor measurements. With the most recent data, a simplified oscillation model (SOM) is evaluated and referred to as an estimated power system model for detection and assessment of an estimated inter-area oscillation mode. Subsequently, an extended SOM is formulated by including dynamic effects of DER control system. The designed controller can be achieved via a metaheuristic method with less effort towards the design specification. Moreover, performance of the designed controller can be evaluated during design to avoid its adverse effects. Some simulation results demonstrate and confirm the applicability and effectiveness of the proposed controller design method. ©2009 IEEE.
Keywords: Controller design; Distributed energy resource; Power system; Synchronized phasor measurement